Preparation and Evaluation of a New Nano Pharmaceutical Excipients and drug Delivery System Based in Polyvinylpyrrolidone and Silicates - Camila Braga Dornelas; Alex Moura Silva; Cide Brizio Dantas; Carlos Rangel Rodrigues; Sandra Solange Coutinho; Plínio Cunha Sathler; Helena Carla Castro; Luiza Rosaria Sousa Dias; Valeria Pereira Sousa; Lúcio Mendes Cabral (Frontiers Media S.A., 2011)
PURPOSE: This work describes the preparation of new nanocomposites based on lamellar silicates (AAM-alkyl ammonium montmorillonite) obtained by the intercalation of PVP K30 and glyceril monostearate. METHODS: By XRD, TGA and DSC analysis the AAM was characterized and its compactation characteristics, functionality and toxicity were also tested. The AAM/PVP K-30 and AAM/GME nanocomposite obtained were evaluated to identify the interlamellar spacing values by XRD diffratograms. Tablets were prepared using methyldopa and theophylline as model drugs and the dissolution tests were carried out in simulated gastric fluid and simulated enteric fluid. RESULTS: AAM showed a good compactability and compressibility characteristics for tablets preparation. The intercalation yields (approximately 25%) of the nanocomposites were efficient. The AAM/PVP K-30 nanocomposites were successfully tested as dissolution enhancers and sustained release matrixes. CONCLUSIONS: The results also suggested the promising use of AAM (viscogel B8) and the new nanocomposite prepared by clay/PVP K-30 intercalation as a new matrix for sustained release and the feasibility of using these new nanocomposites as dissolution enhancer.